Identification of changes in kinematics and electromyographic parameters during dual-task gait: a comparative study between young and elderly female subjects - Camilla Zamfolini Hallal; Deborah Hebling Spinoso; Mary Hellen Morcelli; Ligia Cristiane Fonseca; Mauro Gonçalves; Nise Ribeiro Marques
Abstract Introduction : Falls during gait are one of the leading causes of death and injuries in elderly adults. Objective : This study aimed to compare the performance of young (YG) and elderly (EG) adults during dual-task gait (using a traffic light simulator) according to kinematics and electromyographic parameters. Materials and methods : 17 young and 18 elderly physically fit female subjects participated in this study. The volunteers walked on a treadmill under two different conditions: normal gait (M1) and dual-task gait (M2). We recorded EMG signals from the rectus femoris (RF), vastus medialis (VM), vastus lateralis (VL), biceps femoris (BF), tibialis anterior (TA), gastrocnemius lateralis (GL) and soleus (SO). The following kinematic data were obtained: step length, step time and self-selected velocity. Data analysis was performed using Wilcoxon's, Mann-Whitney, T-student tests and T-student for independent samples. The level of significance was set at p < 0.05. Results : For both groups, there was greater muscle activation of the RF, VM, VL, BF and SO during M2 than during M1. The YG showed lower muscle activation of the RF, VM, BF and SO during M2 when compared to EG. The EG had smaller step length than the YG. The step length values detected during M1 were higher than the ones collected during M2. During M2, the YG showed higher step time compared to the EG. Elderly subjects walked at a lower self-selected velocity than young subjects. Conclusions : Our findings suggest that dual-task gait modify the neuromuscular behavior in elderly subjects, increasing the risk of falls.